2022
DOI: 10.3389/fpls.2022.1017145
|View full text |Cite
|
Sign up to set email alerts
|

Sick or rich: Assessing the selected soil properties and fertility status across the tea-growing region of Dooars, West Bengal, India

Abstract: Harnessing the potential yields of evergreen perennial crops like tea (Camellia sinensis L.) essentially requires the application of optimum doses of nutrients based on the soil test reports. In the present study, the soil pH, organic carbon (OC), available potassium as K2O (AK), and available sulphur (AS) of 7300 soil samples from 115 tea estates spread over the Dooars ranging from 88°52’E to 89°86’E longitude and 26°45’N to 27°00’N latitude of West Bengal, India have been documented. About 54% of soil sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…A degradation test of the hydrogel was performed at pH = 4.5. Our preliminary study revealed that the average pH of dryland soil is 4.50 ( n = 7300, data not shown); 49 therefore, the degradation study was performed at pH 4.5. The degradability test of the hydrogel was measured using the tea bag method.…”
Section: Methodsmentioning
confidence: 98%
“…A degradation test of the hydrogel was performed at pH = 4.5. Our preliminary study revealed that the average pH of dryland soil is 4.50 ( n = 7300, data not shown); 49 therefore, the degradation study was performed at pH 4.5. The degradability test of the hydrogel was measured using the tea bag method.…”
Section: Methodsmentioning
confidence: 98%
“…In India, Dooars is the most famous region for cultivating black tea, upto 32% from West Bengal state. This region is known for Orthodox tea, black teas and CTC (Malakar et al, 2022). Darjeeling tea with a distinct muscatel flavor comes from West Bengal and India.…”
Section: Black Teasmentioning
confidence: 99%
“…Healthy soils for tea gardens frequently have a total nitrogen content of more than 0.1%. The pH of the soil can fluctuate between (4.5 and 5.50) [9]. Two methods are available for determining the type of soil: image analysis and chemical analysis [10].…”
mentioning
confidence: 99%